El Salvador Country Land Assessment - World Bank (Washington, DC, 2014)
This study assesses the alignment of land use, land tenure, and land market outcomes in El Salvador with public policy aspirations in recent decades for efficient, inclusive, and environmentally sustainable development in both urban and rural spaces. In doing so the study indirectly gauges the effectiveness of land sector institutions in facilitating such developmental outcomes in agricultural production, urbanization, and forest management. Chapter 1 briefly reviews some of the prominent struggles over land in El Salvador and outlines the salient features of today's institutional framework for land governance. Chapter 2 asks the question, "How effective have public policy interventions, including the Agrarian Reform, been in reducing rural inequality and tenure insecurity?". Chapter 3 explores what has happened to the lands transferred to Agrarian Reform cooperatives under the last iterations of the Agrarian Reform. Chapter 4 asks the question, "How has land governance in El Salvador responded to the challenges of urban land supply in the last decade?". In Chapter 5 the extent to which urban spatial expansion in El Salvador has been occurring in an inclusive way is explored. Chapter 6 presents the findings of the original analyses of land use in relation to deforestation. Chapter 7 analyzes available land market data in three Departments, Ahuachapan, Santa Ana, and Sonsonate, to identify trends and land use dynamism in the first decade of this century. Chapter 8 looks at the study's empirical findings from a more integrated, cross-sectoral perspective so that their implications for public policy are better understood. The final Chapter of the study presents policy options for consideration by the Government of El Salvador and the country's civil society organizations in order to address the key challenges related to land tenure, land use, and territorial planning.